Effect of Different Mouthwashes on Stain Susceptibility of Resin Composite in Contact with Beverages - Haleh Valizadeh Haghi; Shadieh Molaee; Parinaz Oliyanasab; Khatereh Isazadehfar (Tehran University of Medical Sciences, 2023)
Objectives: This study aimed to investigate the effect of common mouthwashes on the color change of a nanohybrid composite and its further stain susceptibility to Coke and coffee. Materials and Methods: One hundred and fifty composite discs were prepared and initial color values were measured using a spectrophotometer. The specimens were grouped based on the 24h exposure to common mouthwashes including Listerine, chlorhexidine, two types of fluoride mouthwashes (alcohol free and alcohol containing) as well as distilled water as control (N=30). The color change (ΔE1) values were calculated to show the amount of color change caused by mouthwashes. Subsequently, the specimens in each group were subdivided and immersed in the secondary colorant solution (coffee, Coke and, distilled water) for seven days. The total color change (ΔE total) values were obtained to show the stain susceptibility. Statistical analysis was conducted using ANOVA and Tukey's post hoc test. A P-value less than 0.05 was considered statistically significant. Results: The calculated ΔE1 of resin composite was significantly higher for all mouthwash groups than that of the control group; however, all were in the clinically acceptable range. Exposure to Listerine and distilled water caused more staining effects compared to other mouthwashes after immersion in secondary colorant solutions. Regardless of primary mouthwash type, coffee and distilled water caused the highest and the least total discolorations, respectively (P<0.001). Conclusion: All mouthwashes caused a clinically acceptable color change in resin composite; however, further stain susceptibility depended on the mouthwashes but was not higher than distilled water.